Antimicrobial Susceptibility of Glaesserella parasuis to Macrolides and Characterization of erm(T)-Carrying Mobile Elements on Chromosome - Peng Zhang; Changmin Li; Shuna Shang; Ting Huang; Junqi Liu; Qianwen Ge; Xiaoping Liao; Liangxing Fang; Yang Yu (Animals)
Glaesserella parasuis is the etiological agent of Glässer’s disease, which causes high morbidity and mortality in pigs worldwide. Macrolide resistance poses an urgent threat to their treatment, as macrolides are widely used for preventing and treating G. parasuis infections. Here, we determined the susceptibilities to five macrolides and characterized the genetic markers of macrolide resistance. The antimicrobial susceptibility of 117 G. parasuis isolates to erythromycin, tulathromycin, gamithromycin, tylosin, and tilmicosin was evaluated using broth microdilution method. Erythromycin-resistant isolates were sequenced using whole-genome sequencing. Further analysis of these sequences revealed the genetic basis of macrolide resistance in G. parasuis. Our results show that most G. parasuis isolates remained susceptible to the macrolide drugs. For commonly used agents (e.g., tylosin and tilmicosin), elevated minimum inhibitory concentrations (MICs) were observed, whereas for the newer macrolides (e.g., tulathromycin and gamithromycin), the MICs remained almost unchanged. The macrolide resistance gene erm(T) and the A2059G mutation in 23S rRNA were detected in the current study. To the best of our knowledge, integrative and conjugative element (ICE)-borne erm(T) in G. parasuis is reported for the first time in this study. Taken together, these results provide insights into the susceptibility of G. parasuis to macrolides. The presence of erm(T) on ICEs may facilitate its transfer, reducing the effectiveness of macrolide treatment.